Perancangan dan Implementasi Sistem Informasi Kesehatan P - IRT berbasis Web dan Android - Yan Rigid Wijaya; Radius Tanone (Maranatha University Press, 2020)
The Salatiga City Government through the Health Office organizes a system of services and socialization to the community in a preventive manner. The intended community includes P-IRT (Food and Home Industry) which constitutes the food and beverage industry sector which is included in the small industry. In carrying out the delivery of information, employees must carry out a program of training activities as well as by conducting socialization to the community directly, where it is more time consuming, costly, and energy. This also makes the service and delivery of information less efficient. Therefore a web-based and mobile-based information system design is needed to complement these shortcomings. By using the Laravel Framework and Android Programming as well as a collaborative filter algorithm, a web-based application and an Android phone are generated to address the problem. Sharing information and discussions between the public and related agencies is easier to use this system.